The contribution of job characteristics, working environment and organization culture towards work stress at Hospital Penawar Sdn Bhd. / Julia Sa’ayon - Sa’ayon, Julia (Faculty of Business and Management, 2012)
Stress in organizations is a very critical phenomenon. Work stress commonly can be define as harmful physical and emotional responses that occur when the requirements of a job match the capabilities, resources or needs of the worker. Work stress can lead to poor health or injury towards the employee and will invite an uncomfortable working environment. There are three factors that may contribute to Work Stress and the management should assess and learn that factor. The factors that will be discuss in this study are Job Characteristics, Working Environment and Organization culture. This study consists of the analysis on the relationship between the variable and is there any relationship between them. Pearson Correlation is used to determine the strength of relationship between dependent variable and independent variable. The researcher getting data from questionnaire and that are distributed to all level management of Hospital Penawar Sdn Bhd. Coefficient Correlation shows among three elements of Work Stress only Working Environment shows the most significant relationship and the other two also has a significant relationship but very weak. Some recommendation were given in this research such as Open communication channels between supervisor and their employees, and make sure that the employee encouragement to discuss their concern and the supervisor can valued their suggestion to reduce the Work Stress that they faced. Monitoring is essential to determine progress towards achieving goals, it also useful to monitor the level of stress that will happened among the employee, and hopefully there will be a continuous research about this topic and for future researcher they will take a look at whole industry not just on services industry they also can look from manufacture company